GRAPHIC DESIGN WORKSHOP USING CANVA TO INCREASE CREATIVITY AND ABILITY OF STUDENTS OF SMK AND MTS AR-RIZKHAN - Roby Setyadi; Siwi Nur; Rina Kariyani; Rahmanto Dwi Sasongko; Annisa Annisa; Lelly Qodariah (Universitas PGRI Sumatera Barat, 2022)
In this sophisticated and digital era of globalization, studying graphic design is important and beneficial for students. By studying graphic design, you are able to grow and shape your creativity so that you can come up with interesting and unique ideas to improve your welfare. Making logo designs and work content is one of the activities that students can use as soft skills in the world of work. The graphic design training activity using Canva at MTS and SMK Ar-Rizkhan aims to provide knowledge related to graphic design and help students to be creative in using Canva. The Canva app is an online, free, and easy-to-use graphic design application. The method of implementing graphic design training activities at MTS and SMK Ar-Rizkhan uses three stages, namely material, theory/practicum, and evaluation. It is hoped that this graphic design training activity will make students more enthusiastic about creativity in the field of graphic design and can open up business opportunities, either goods or services independently.